Paradoxical Leader Behaviors in People Management: Antecedents and Consequences - Zhang, Yan; Waldman, David A.; Han, Yu-Lan; Li, Xiao-Bei (Academy of Management Journal, 2015)
As organizational environments become increasingly dynamic, complex, and competitive, leaders are likely to face intensified contradictory, or seemingly paradoxical, demands. We develop the construct of “paradoxical leader behavior” in people management, which refers to seemingly competing, yet interrelated, behaviors to meet structural and follower demands simultaneously and over time. In Study 1, we develop a measure of paradoxical leader behavior in people management using five samples from China. Confirmatory factor analyses support a multidimensional measure of paradoxical leader behavior with five dimensions: (1) combining self-centeredness with other-centeredness; (2) maintaining both distance and closeness; (3) treating subordinates uniformly, while allowing individualization; (4) enforcing work requirements, while allowing flexibility; and (5) maintaining decision control, while allowing autonomy. In Study 2, we examine the antecedents and consequences of paradoxical leader behavior in people management with a field sample of 76 supervisors and 516 subordinates from 6 firms. We find that the extent to which supervisors engage in holistic thinking and have integrative complexity is positively related to their paradoxical behavior in managing people, which, in turn, is associated with increased proficiency, adaptivity, and proactivity among subordinates.